2005
DOI: 10.1017/s0016756805001391
|View full text |Cite
|
Sign up to set email alerts
|

The Beothuka terranova (Radiolaria) assemblage and its importance for the understanding of early Ordovician radiolarian evolution

Abstract: The radiolarian Beothuka terranova occurs in the Arenigian Didymograptellus bifidus Biozone (uppermost Lower Ordovician) of Spitsbergen (Svalbard), associated with a diverse and wellpreserved radiolarian fauna. The presence of typical Cambrian spicular radiolarians associated with derived spherical forms shows a gradational faunal change from the Cambrian to the Ordovician. The genus and species Antygopora ordovicica n. gen. et n. sp. is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 28 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…1). This level compares to the Yapeenian to Lower Darriwilian (Maletz and Bruton 2005) or the Upper Arenig to Lower Llanvirn as first suggested by Fortey and Holdsworth (1971). The authors reported radiolarians from three levels within an interval of five meters, but did not document these faunas separately.…”
Section: The Spitsbergen Faunasupporting
confidence: 50%
See 4 more Smart Citations
“…1). This level compares to the Yapeenian to Lower Darriwilian (Maletz and Bruton 2005) or the Upper Arenig to Lower Llanvirn as first suggested by Fortey and Holdsworth (1971). The authors reported radiolarians from three levels within an interval of five meters, but did not document these faunas separately.…”
Section: The Spitsbergen Faunasupporting
confidence: 50%
“…It was interpreted to be of mid‐Arenig age based on the close proximity to levels with the Upper Bendigonian to Chewtonian graptolite fauna 5 of Stone and Smellie (1988). Maletz and Bruton (2005) referred the Proventocitum procerulum assemblage to the Lower to Middle Darriwilian, based on the observation that the assemblage differs considerably from Chewtonian to Castlemainian (Upper Floian to Lower Dapingian) assemblages of western Newfoundland and Spitsbergen. A comparison of radiolarian assemblages from the Lower to Middle Ordovician is here attempted to get a better idea on the exact biostratigraphic distribution of the Proventocitum procerulum assemblage and to understand its composition.…”
mentioning
confidence: 99%
See 3 more Smart Citations